Dust Formation in Astrophysical Environments: The Importance of Kinetics - Tielens, A.G.G.M. (Frontiers in Astronomy and Space Sciences, 2022)
Astronomical observations and analysis of stardust isolated from meteorites have revealed a highly diverse interstellar and circumstellar grain inventory, including a wide range of amorphous materials and crystalline compounds (silicates and carbon). This diversity reflects the wide range of stellar sources injecting solids into the interstellar medium each with its own physical characteristics such as density, temperature and elemental composition and highlights the importance of kinetics rather than thermodynamics in the formation of these compounds. Based upon the extensive literature on soot formation in terrestrial settings, detailed kinetic pathways have been identified for the formation of carbon dust in C-rich stellar ejecta. These have been incorporated in astronomical models for these environments. In recent years, the chemical routes in the nucleation of oxides and silicates have been the focus of much astronomical research. These aspects of stardust formation will be reviewed and ``lessons’’ for dust formation in planetary atmospheres will be drawn with the emphasis on the influence of kinetics on the characteristics and structure of dust in these environments.